Minat Mahasiswa Akuntansi Berwirausaha di Kota Mataram: Dampak Pemahaman E-Commerce, Pengetahuan Kewirausahaan dan Penggunaan Sistem Informasi Akuntansi - Ida Ayu Dwi Indriani Astuti; Agus Khazin Fauzi; Sofiati Wardah; Anna Apriana Hidayanti (eCo-Fin, 2025)
This study aims to test and analyze the effect of understanding e-commerce, entrepreneurial knowledge and the use of accounting information systems on accounting students' interest in entrepreneurship. Accounting students in 5 universities in Mataram City became the population and sample in this study with the Slovin technique used in determining the minimum sample and proportionate random sampling as a method of distributing questionnaires to respondents. Multiple linear regression analysis with SPSS 25 was used in testing this research. Based on the test results that have been carried out, it is found that the variables of understanding e-commerce, entrepreneurial knowledge and the use of accounting information systems have a significant effect on the interest of accounting students in entrepreneurship. It can be explained that the three variables used play an important role in strengthening the readiness and chances of student success in entrepreneurship so as to reduce unemployment in Indonesia, which means that student orientation is no longer a job seeker but instead a job creator. Based on the results of R square found that 51.6% of the variables of understanding e-commerce, entrepreneurial knowledge and the use of accounting information systems are able to contribute to the interest of accounting students in entrepreneurship, while the remaining 48.4% is explained by other variables that are not included in this research variable such as expectations.